Efficiency enhancement of non-fullerene organic solar cells using PEDOT:PSS diluted with alcohol solvents as the hole transport layer - Han, Tingting; Gao, Chuanlin; Sun, Kangbo; Zhu, Liangxiang; Wang, Lihong; Liang, Wenting; Miao, Yanqin; Wang, Yufei; Qiu, Mingxia; Li, Shunpu; Zhang, Guangye (Frontiers in Materials, 2024)
Poly (3,4-ethylenedioxythiophene)-poly (styrene sulfonate) (PEDOT:PSS) hole transport layer (HTL) has always played a crucial role in achieving high-efficiency organic solar cells (OSCs), owing to the unique advantages of suitable energy level and high optical transparency. However, due to the inherent insulation and easy aggregation property of PSS, leading to the relatively low conductivity and high surface roughness of PEDOT:PSS film, which is unfavorable for charge transport and morphology of the top layer. To address the aforementioned problems, we employ a series of alcoholic solvent diluted PEDOT:PSS and practice them on the PM6:Y6 system. Among them, the PM6:Y6 devices using PEDOT:PSS modified with ethanol as HTL demonstrate the best vertical phase segregation and carrier extraction. In addition, the PEDOT:PSS film with added ethanol also shows the smoothest surface compared with other alcoholic solvents. Finally, a high PCE of 18.13% was obtained in PM6:Y6 devices based on PEDOT:PSS modified by ethanol. This work provides a sufficient reference on the alcohol modification of PEDOT:PSS, and also points out a feasible solution for high-efficiency organic solar cells